PENINGKATAN KEMAMPUAN KOMUNIKASI RELAWAN SOSIAL DESA TANJUNGWANGI, KECAMATAN CICALENGKA, KABUPATEN BANDUNG MELALUI TEKNIK PUBLIC SPEAKING - Charisma Asri Fitrananda; Iing Saefudin; Mochamad Iqbal (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Mataram, 2021)
This service aims to empower the Social Volunteers of Tanjungwangi Village, Cicalengka District, Bandung Regency in improving their public speaking skills. The ability to speak in public is an important part of every activity, especially activities in social settings. In fact, there are still very few social volunteers who have public speaking skills in carrying out their duties in various social activities. From this, the Community Service Team for the Communication Science Study Program of Universitas Pasundan took the initiative to carry out community service with the theme of Improving the Communication Ability of Social Volunteers in Tanjungwangi Village, Cicalengka District, Bandung Regency, West Java Province through Public Speaking Techniques. The location selection is inseparable from the large number of community social volunteers who wish to have the ability to speak in front of the general public and presentation techniques during counseling but have not yet been honed. The method used in this training is to present material, discussion, and simulation. The problems faced by partners are partners who do not yet have the ability to make materials or materials for counseling, partners have not been able to communicate effectively using public speaking techniques. This service activity uses a contextual approach, namely giving theory first and providing direction and mentoring partners in making outreach materials, preparing presentations, and public speaking techniques. Then with the facilitating method in content containing counseling, information, and education materials in the form of writing and video through social media.